# If x+iy=a+ib/a-ib, prove that x2+y2=1?

### 2 Answers

- rotchmLv 73 weeks ago
x+iy=(a+ib)/(a-ib). Take the conjugate each side to get

x - iy = (a-ib)/(a+ib). Now multiply the RHS's together & LHS's together to get

(x+iy)(x-iy) = (a+ib)(a-ib) / ( (a-ib)(a+bi) ). Expand & simplify to get

x² + y² = (a² + b²)/(a² + b²). What does the RHS equal?

Done!

- 3 weeks ago
I presume you mean (a + ib) / (a - ib) and x^2 + y^2 = 1

x + iy = (a + ib) / (a - ib)

x + iy = (a + ib)^2 / (a^2 - i^2 * b^2)

x + iy = (a + ib)^2 / (a^2 + b^2)

x + iy = (a^2 + 2abi - b^2) / (a^2 + b^2)

x = (a^2 - b^2) / (a^2 + b^2)

y = 2ab / (a^2 + b^2)

x^2 + y^2 =>

(a^2 - b^2)^2 / (a^2 + b^2)^2 + (2ab)^2 / (a^2 + b^2)^2 =>

((a^2 - b^2)^2 + (2ab)^2) / (a^2 + b^2)^2 =>

(a^4 - 2a^2 * b^2 + b^4 + 4a^2 * b^2) / (a^2 + b^2)^2 =>

(a^4 + 2a^2 * b^2 + b^4) / (a^2 + b^2)^2 =>

(a^2 + b^2)^2 / (a^2 + b^2)^2 =>

1